2018
DOI: 10.1371/journal.pbio.2004356
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic combination efficacy (ACE) networks for a Pseudomonas aeruginosa model

Abstract: The spread of antibiotic resistance is always a consequence of evolutionary processes. The consideration of evolution is thus key to the development of sustainable therapy. Two main factors were recently proposed to enhance long-term effectiveness of drug combinations: evolved collateral sensitivities between the drugs in a pair and antagonistic drug interactions. We systematically assessed these factors by performing over 1,600 evolution experiments with the opportunistic nosocomial pathogen Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
98
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 54 publications
7
98
0
Order By: Relevance
“…These results indicate that drug interactions underlie a natural trade-off between short-term efficacy and long-term evolutionary potential (38). In addition, recent work has shown that cross-resistance (or collateral sensitivity) between drugs in a combination may also significantly modulate resistance evolution (27,39,26). As a whole, these studies show that drug interactions and collateral effects may combine in complex ways to influence evolution of resistance in multi-drug environments.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…These results indicate that drug interactions underlie a natural trade-off between short-term efficacy and long-term evolutionary potential (38). In addition, recent work has shown that cross-resistance (or collateral sensitivity) between drugs in a combination may also significantly modulate resistance evolution (27,39,26). As a whole, these studies show that drug interactions and collateral effects may combine in complex ways to influence evolution of resistance in multi-drug environments.…”
Section: Introductionmentioning
confidence: 74%
“…In recent years, significant efforts have been devoted to designing evolutionarily sound strategies that balance short-term drug efficacy with the long-term potential to develop resistance. These approaches describe a number of different factors that could modulate resistance evolution, including interactions between bacterial cells (3,4,5,6,7,8), synergy with the immune system (9), spatial heterogeneity (10,11,12,13,14,15), epistasis between resistance mutations (16,17), precise temporal scheduling (18,19,20,21), and statistical correlations between resistance profiles for different drugs (22,23,24,25,26,27,28,29,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the possibility that local environmental conditions could influence both the emergence of collateral sensitivity (by affecting which of the possible pathways to resistance are most strongly selected during antibiotic exposure) and its expression (by modifying the phenotypic effects of resistance alleles when bacteria are exposed to a second antibiotic). To date, research on collateral sensitivity interactions has focused on testing many combinations of antibiotics 5,6,9,14 , multiple strains 10 , or many replicate populations for individual antibiotic combinations 11 . Therefore, the role of local abiotic conditions in the emergence and expression of collateral sensitivity interactions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These anti-resistance approaches exploit different features of the population dynamics, including competitive suppression between sensitive and resistance cells (14,15), synergy with the immune system (16), precise timing of growth dynamics or dosing (17,18), responses to subinhibitory drug doses (19), and band-pass response to periodic dosing (10). Resistance-stalling strategies may also exploit spatial heterogeneity (20,21,22,23,24,25), epistasis between resistance mutations (26,27), hospital-level dosing protocols (28,29), and regimens of multiple drugs applied in sequence (28,30,18,31,19,32) or combination (33,34,35,36,37,38,39,40), which may allow one to leverage statistical correlations between resistance profiles for different drugs (41,42,43,44,39,37,45,46,47,48). As a whole, these studies demonstrate the important role of community-level dynamics for understanding and predicting how bacteria respond and adapt to antibiotics.…”
Section: Introductionmentioning
confidence: 99%